No Evidence of Association between Toxoplasma gondii Infection and Financial Risk Taking in Females - Lanchava, Lasha; Carlson, Kyle; Šebánková, Blanka; Flegr, Jaroslav; Nave, Gideon (PloS one, 2015)
BACKGROUND: Past research linked Toxoplasma gondii (TG) infection in humans with neurological and mental disorders (e.g., schizophrenia, Alzheimer's disease and attention disorders), irregularities of the dopaminergic and testosterone system, and increased likelihood of being involved in traffic accidents. METHODOLOGY/PRINCIPAL FINDINGS: We test for an association between TG infection and financial decision-making (DM) using a case-control design in a sample of female Czech students (n = 79). We estimate each subject's risk attitude and loss aversion using an experimental economic task involving real monetary incentives. We find no significant evidence that either measure of decision-making is associated with TG infection. CONCLUSION: We were unable to find evidence of an association between TG infection and financial decision-making in females.
Keywords: Financial Management; krevní skupiny - systém Rh-Hr; Decision Making; studie případů a kontrol; Sex Factors; toxoplazmóza; Humans; Female; mladiství; Rh-Hr Blood-Group System; Case-Control Studies; ženské pohlaví; rozhodování; mladý dospělý; Adult; Young Adult; Toxoplasmosis; riskování; Risk-Taking; sexuální faktory; Adolescent; dospělí; lidé; finanční řízení